2019
DOI: 10.1680/jemmr.18.00093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber and resin types on mechanical properties of fiber-reinforced composite pipe

Abstract: The aim of this study was to evaluate the effects of the types of fiber and resin on the mechanical properties of polyester composite pipes. Orthophthalic, isophthalic and vinyl ester resins were used as the matrix; E-glass, electrical/chemical resistance (ECR)-glass and basalt fibers were used as reinforcement; and 98% silica (SiO2) sand was used as filler in mixtures. Samples were produced by the centrifugal casting method. Samples cut from the produced pipes were tested to determine stiffness and longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Furthermore, it was concluded that the low‐content graphene platelets additive increased the number of fatigue cycles and improved fatigue life. In the study conducted by Gokce et al, [ 20 ] experimental studies were carried out to determine the effects of matrix and fiber materials on the mechanical properties of composite pipes. Orthophthalic, isophthalic, and vinyl ester resins were used as matrix material, while E‐glass, electrical/chemical resistance (ECR)‐glass and basalt fibers were used as fiber material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it was concluded that the low‐content graphene platelets additive increased the number of fatigue cycles and improved fatigue life. In the study conducted by Gokce et al, [ 20 ] experimental studies were carried out to determine the effects of matrix and fiber materials on the mechanical properties of composite pipes. Orthophthalic, isophthalic, and vinyl ester resins were used as matrix material, while E‐glass, electrical/chemical resistance (ECR)‐glass and basalt fibers were used as fiber material.…”
Section: Introductionmentioning
confidence: 99%
“…Some design parameters such as stacking sequence, [16][17][18][19] fiber material, [20] fiber orientation [21] and nanomaterial additive [22] are significantly effective on the mechanical properties of the composite overwrapped pressure vessels and composite pipes. Therefore, many studies have been carried out to determine the effect of design parameters on mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that first-ply-failure and functional failure pressures increase linearly as the core thickness increase. Gökçe et al [16] analysed the effects of the type of resin and fiber on the mechanical behaviours of the polymer composite pipe manufactured by the CC technic. Isophthalic, ortophthalic, and vinyl ester resin were used as matrix material, E and ECR glass fiber were used as reinforcement material, and silica sand was used as filler material.…”
Section: Introductionmentioning
confidence: 99%